Security Mechanism for Dual Stack Network Accessing of Home Gateway - Zhonghua Chen (Dianxin kexue)
With the exhaust of IPv4 address, internet is transferring to IPv6. Firstly, security problems of home gateway in the dual stack accessing scene were analyzed, including IPoE service channel protection, dual stack address pool tracing, and manage port address protection. Secondly, three methods were given to solve the security problems. At last, a realization and experiment result was given.